In-vivo evaluation and formulation development of polyherbal extract in streptozotocin-induced diabetic rat - Sagarika Majhi; Lubhan Singh; Madhu Verma; Iti Chauhan; Raj kumari; Meenakshi Sharma (Elsevier, 2022)
Background: The research focuses on polyherbal antidiabetic extracts from various plants that are utilized in the management of type 2 diabetes mellitus at various doses. Ayurvedic treatment is widely accepted throughout due to their efficacy, safety, less price, ubiquity, and acceptance. Polyherbal medicines, contain glycosides, alkaloids, flavonoids, and other compounds that have unique mode of action to treat diabetes, have long been used across the world. This study was carried out to investigate the hypoglycemic effects and antihyperglycemic activity of polyherbal (PH) extract in streptozotocin (STZ)-induced diabetic rats. Along with this, the antioxidant and antihyperlipidemic activity of Polyherbal extract (PH) were also studied. Further, polyherbal tablets were formulated and evaluated. Method: Polyherbal extract (hydroalcoholic) was tested for the hypoglycemic activity for 4 h in normoglycemic rats, oral glucose tolerance test (OGTT) (2 h), and antihyperglycemic activity (28 days) in non-diabetic and STZ-induced diabetic rats. Further, antihyperlipidemic and antioxidant activity were also studied along with histopathology and pre & post-compression tablet data. The effective antidiabetic activity was observed for PH I (400 mg/kg followed 200 mg/kg). OGTT has shown that PH I (200 mg/kg) extract is having a better glucose utilization capacity. The data also propose that PH I (400 mg/kg followed 200 mg/kg) exhibit significant and consistent hypoglycemic activity. Results: Our findings explain that polyherbal extract in variant doses has antihyperlipidemic and antioxidant activity, which is manifested by decreasing total cholesterol, triglyceride, LDL, VLDL and MDA level. The extract also increased the HDL, SOD and reduced glutathione level in various treatment groups. The data propose that the combined extract showed a consistent and ameliorated hepatic and renal function, in the treatment groups. Polyherbal extract PH I (400 mg/kg) have manifested the most effective improvements in diabetic complications. All the pre & post-compression tablet data were within limits. The above results propose that this Polyherbal extract may be a potential source for the development of the new antidiabetic drug. Conclusions: The proposed activity of the polyherbal extract is supported by various biochemical and histopathologic analyses. By examining its safety and in vivo efficacy, the combination of ayurvedic components will give us a novel glimmer of hope for the lifestyle illness.